Application of the Thomas precession to the deformations of a rotating disk - Celakoska, E.G.; Trecevski, K.; Balan, V. (Український математичний вісник, 2009)
Within the framework of Special Relativity, the recent paper [1] describes the shrinking determined by the rotation of a planar disk, and an apparent paradox emerging from the anisotropic outcoming contraction. In this paper, using the Thomas precession, we obtain the same result in a different way.